2016
DOI: 10.1063/1.4948996
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional quantum dynamics study of the H2 + C2H → H + C2H2 reaction on an ab initio potential energy surface

Abstract: This work performs a time-dependent wavepacket study of the H2 + C2H → H + C2H2 reaction on a new ab initio potential energy surface (PES). The PES is constructed using neural network method based on 68 478 geometries with energies calculated at UCCSD(T)-F12a/aug-cc-pVTZ level and covers H2 + C2H↔H + C2H2, H + C2H2 → HCCH2, and HCCH2 radial isomerization reaction regions. The reaction dynamics of H2 + C2H → H + C2H2 are investigated using full-dimensional quantum dynamics method. The initial-state selected rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Experimental and theoretical studies on the tunneling splitting found that the minima are connected by a straight Y-shaped C2v transition state, [2] ‡ , along the CCH bending mode. The electronic energy of this transition state has been reported to be about 0.21 eV above that of the global minimum in various experimental 8,9 and computational [10][11][12][13][14] works. After years of quantum chemical research, a consensus has emerged that, similarly to the ethyl cation, 15 the vinyl cation also has a non-classical C2v global minimum with a proton bridging the two carbon atoms, [3] + .…”
Section: Introductionmentioning
confidence: 90%
“…Experimental and theoretical studies on the tunneling splitting found that the minima are connected by a straight Y-shaped C2v transition state, [2] ‡ , along the CCH bending mode. The electronic energy of this transition state has been reported to be about 0.21 eV above that of the global minimum in various experimental 8,9 and computational [10][11][12][13][14] works. After years of quantum chemical research, a consensus has emerged that, similarly to the ethyl cation, 15 the vinyl cation also has a non-classical C2v global minimum with a proton bridging the two carbon atoms, [3] + .…”
Section: Introductionmentioning
confidence: 90%
“…By using the recent ab initio potential energy surface of Chen et al, 89 we have accuately calculated the lowest hundreds of rovibrational states of C 2 H 3 . The results will be published elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…were investigated using the full-dimensional ISSWP method on a new ab initio PES 197 . This PES was constructed using neural network method based on roughly 70 000 data points calculated at UCCSD(T)-F12a/AVTZ level and covers H2+C2H ↔ H+C2H2, H+C2H2 → HCCH2, and HCCH2 radial isomerization reaction regions.…”
Section: H2+c2h → H+c2h2mentioning
confidence: 99%